Managing Siting Activities for Nuclear Power Plants. - IAEA (International Atomic Energy Agency, 2022)
Member States continue to request guidance on introducing nuclear power to their power production strategy. This publication provides updated methodology and framework and discusses aspects including nuclear safety and security, technology and engineering, economics and cost, land use planning and preparation, socioeconomic impacts and involvement of stakeholders.
Keywords: Nuclear power plants -- Location.; elektronické knihy; electronic books